2012
DOI: 10.2337/db11-1763
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of TNF-α Improves the Bladder Dysfunction That Is Associated With Type 2 Diabetes

Abstract: Diabetic bladder dysfunction (DBD) is common and affects 80% of diabetic patients. However, the molecular mechanisms underlying DBD remain elusive because of a lack of appropriate animal models. We demonstrate DBD in a mouse model that harbors hepatic-specific insulin receptor substrate 1 and 2 deletions (double knockout [DKO]), which develops type 2 diabetes. Bladders of DKO animals exhibited detrusor overactivity at an early stage: increased frequency of nonvoiding contractions during bladder filling, decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 41 publications
10
72
0
1
Order By: Relevance
“…These findings are supported by a previous study implicating this cytokine in developing bladder dysfunction in an animal model of type 2 diabetes, which is associated with bladder hypertrophy and overactivity (31). Similarly, studies using detrusor smooth muscle cells showed that TNF-α and IL-1β induced secretion of IL-8 and IL-6 (32), in line with our data in BOO patients.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are supported by a previous study implicating this cytokine in developing bladder dysfunction in an animal model of type 2 diabetes, which is associated with bladder hypertrophy and overactivity (31). Similarly, studies using detrusor smooth muscle cells showed that TNF-α and IL-1β induced secretion of IL-8 and IL-6 (32), in line with our data in BOO patients.…”
Section: Discussionsupporting
confidence: 82%
“…Proinflammatory cytokines are essential in stimulating the angiogenic, lineage-specific differentiation, proliferative, and immunomodulatory functions of stem cells. Interleukin (IL) 1α and β, tumor necrotic factor (TNF) α, and interferon are examples of proinflammatory markers that play roles in kidney fibrosis, cancers, bladder obstruction, and other urologic diseases [84][85][86][87]. Recent studies in our lab showed that hypoxia treatment of normal bladder smooth muscle cells results in a time-dependent increase in endogenous TNFα levels.…”
Section: Paracrine Effects Of Stem Cells On Urologic Factorsmentioning
confidence: 97%
“…Overactive bladder is often associated with detrusor overactivity, an urodynamic observation characterized by involuntary detrusor contractions during the filling phase, which may be spontaneous or provoked (Irwin et al, 2006). Obese animals exhibit cystometric alterations such as increases in the frequency of voiding and non-voiding contractions, along with in vitro detrusor overactivity Rahman et al, 2007;Wang et al, 2012). Urethral smooth muscle dysfunction due to impairment of the nitric oxide signal transduction also occurs in conditions of obesity .…”
Section: Introductionmentioning
confidence: 97%
“…Obesity has been described as a low-grade chronic inflammation associated with cardiovascular diseases and diabetes along with premature mortality (Apostolopoulos et al, 2016;Wang et al, 2012). Clinical studies have also implicated obesity as a major contributing factor for the lower urinary tract symptoms (Steers, 2009), which comprises storage, voiding or post micturition symptoms (Irwin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%